P43. Heart rate variability is decreased in patients with amyotrophic lateral sclerosis. Issue 8 (August 2015) - Prell, T.; Ringer, T.; Witte, O.W.; Grosskreutz, J.
<x xml:space="preserve">Abstract</x> Introduction There is increasing evidence that amyotrophic lateral sclerosis (ALS) is a multisystem disease and that pathological processes extend beyond the motor system. Because the disease is not curable, patients usually die within 3 years due to respiratory failure. However, also autonomic dysfunction has been reported in ALS, in particular in advanced stages of the disease. Probably cardiovascular dysfunction related to dysautonomia is a cause of sudden cardiac arrest or anoxic encephalopathy after circulatory collapse in these patients. Methods We performed a retrospective review of standard polygraphy recordings (Somnoscreen, SOMNOmedics, Randersacker, Germany) of 80 ALS patients. Sleep was staged by personnel blinded to the protocol using standard techniques for scoring sleep stages and arousals. Time-domain parameters of heart rate variability (HRV), such as mean RR interval, SDNN were obtained from nocturnal ECG monitoring. R-R intervals were calculated from artifact and apnea/hypopnea-free periods by the detection of QRS complexes. Results HRV variability was found to be reduced in ALS patients. ALS patients are characterized by a marked increase in heart rate. Conclusion Our results confirm impaired cardiac autonomic control in ALS. The observed parasympathetic dysfunction and sympathetic predominance could be an explanation of sudden cardiac death.